2013
DOI: 10.1007/s00268-013-2247-7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Posthepatectomy Liver Failure on the Recurrence of Hepatocellular Carcinoma

Abstract: EPLF was associated with postoperative HCC recurrence. The prevention of EPLF might improve the prognosis of patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
(63 reference statements)
1
17
0
Order By: Relevance
“…This results in liver dysfunction and failure, which can even lead to death via multiorgan system failure. Furthermore, tissue damage of the liver parenchyma induced by ischemia/reperfusion (I/R) can potentially lead to postoperative cancer recurrence …”
mentioning
confidence: 99%
“…This results in liver dysfunction and failure, which can even lead to death via multiorgan system failure. Furthermore, tissue damage of the liver parenchyma induced by ischemia/reperfusion (I/R) can potentially lead to postoperative cancer recurrence …”
mentioning
confidence: 99%
“…After ISGLS defined PHLF, Iguchi et al [12] reported significant differences in the duration of surgery (>300 min) and blood loss (>800 mL) between grade A and grades B/C PHLF [Iguchi, 2014]. Fukushima et al [5] reported major hepatectomy, intraoperative blood loss (>1,000 mL) and stage 3 fibrosis as independent risk factors for PHLF, according to the ISGLS definition [5].…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have investigated the independent risk factors for PHLF using the classification criteria by ISGLS. For example, Fukushima et al [5] reported extent of resection, intraoperative blood loss and fibrosis stage as independent risk factors for the development of PHLF; whereas Iguchi et al [12] showed significant differences in blood loss and duration of surgery between grade A and grade B/C patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In establishing new criteria, we accepted the occurrence of grade A PHLF and grade B PHLF with a probability of approximately 20% ( table 4 ). Although PHLF has a negative impact on DFS and OS in patients with HCC [33,34] , no treatments (with the exception of hepatectomy) provide a longer survival benefit for patients with a high risk of PHLF after hepatectomy. A patient with grade A or B PHLF is able to recover from PHLF and rehabilitate within a few months after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%